Nucleated red blood cells for characterization of systemic inflammatory response syndrome in dogs - ARom Cho; Hyeona Bae; Youngju Kim; Yeseul Jeon; Rankyung Jung; Minji Kim; Minjeong Kang; Sumin Cha; Kyu‐Woan Cho; Dong‐In Jung; Jinho Park; DoHyeon Yu (Journal of Veterinary Internal Medicine)
Abstract Background Nucleated red blood cells (nRBCs) are increased by disease processes and hematopoietic stress. Objectives To evaluate the utility of nRBCs as a marker of disease severity and prognosis in dogs with systemic inflammatory response syndrome (SIRS). Animals Sixty‐two client‐owned dogs met the criteria of SIRS without anemia. Methods nRBC‐positive (nRBCs: ≥5/500, n = 32) and nRBC‐negative (nRBCs: <5/500, n = 30) dogs were classified, and clinicopathological data, Acute Patient Physiologic and Laboratory Evaluation (APPLEfast) scores, cytokines, 2‐ and 4‐weeks survival were compared. Results The median WBC (17.63, interquartile range [IQR]: 11.72‐20.24 × 109/L), neutrophils (12.28, IQR: 7.17‐16.88 × 109/L), band neutrophils (1288.5, IQR: 252.5‐2575 cells/μL), serum IL‐6 (731.80, IQR: 299.79‐5522.05 pg/mL), and plasma C‐reactive protein (4.10, IQR: 1.00‐8.58 mg/L) were significantly higher in nRBC‐positive dogs than negative dogs (11.27, IQR: 7.63‐15.13 × 109/L; 7.57, IQR: 4.96‐11.71 × 109/L; 62.5, IQR: 0‐350.25 cells/μL; 232.30, IQR: 99.33‐447.01 pg/mL; 0.40, IQR: 0.10‐3.00 mg/L, respectively; P < .05). The median reticulocyte count (87.95, IQR: 52.45‐130.55 × 103/μL) and serum IL‐3 (40.94, IQR: 29.85‐53.52 ng/L) were also significantly greater in nRBC‐positive dogs than nRBC‐negative dogs (46.00, IQR: 26.43‐68.15 × 103/μL; 25.24, IQR: 21.65‐37.40 ng/L, respectively; P < .01). The presence of circulating nRBCs, but not the reticulocyte count, at admission was predictive of death in dogs with SIRS at 2 weeks (P = .01, AUC: 0.729) and 4 weeks (P = .002, AUC: 0.731). The overall survival time was shorter in nRBC‐positive dogs (95% CI, 47.35‐113.90) than nRBC‐negative dogs (95% CI, 90.92‐135.55; P = .03). Conclusions and Clinical Importance Measuring peripheral nRBCs in dogs with SIRS is rapid and clinically applicable, reflecting disease severity and associated prognosis.